2019
DOI: 10.17221/87/2018-swr
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the soil structure of the piedmont-plains by the fractal dimension of particle size

Abstract: Soil structure fundamentally determines the hydrodynamic characteristics of the saturated–unsaturated zone, solute transport characteristics, and thermodynamic properties of the soil. Additionally, it regulates the process of transfer and conversion of matter and energy in the saturated–unsaturated zone. However, the quantification of soil structure is difficult because it depends on a combination of factors including soil particle sizes and types and spatial distribution of pores. In this study, the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This is well confirmed in this study as well. The fractal dimension decreases with the increase in soil depth, which may be related to the high content of litter in surface soil and the spatial distribution of organic matter [42]. This study shows that the multifractal dimension of the mixed forest is greater than that of the monospecies forest, and that of the broad-leaved forest is greater than that of the coniferous forest.…”
Section: Effects Of Four Vegetation Restoration Types On Fractal Para...mentioning
confidence: 67%
See 2 more Smart Citations
“…This is well confirmed in this study as well. The fractal dimension decreases with the increase in soil depth, which may be related to the high content of litter in surface soil and the spatial distribution of organic matter [42]. This study shows that the multifractal dimension of the mixed forest is greater than that of the monospecies forest, and that of the broad-leaved forest is greater than that of the coniferous forest.…”
Section: Effects Of Four Vegetation Restoration Types On Fractal Para...mentioning
confidence: 67%
“…However, some scholars have studied relationship between the soil fractal dimension and physicochemical properties in the Loess Plateau. They found that the fractal dimension was negatively correlated with porosity and positively correlated with bulk density [42]. This may be related to the different environmental factors such as climate and soil in the study area, or it may be caused by different vegetation restoration types in the study area.…”
Section: Infuluence Of Four Vegetation Restoration Types On Soil Psd ...mentioning
confidence: 92%
See 1 more Smart Citation
“…The soil particle size distribution (PSD) reflects the process of soil weathering and formation, which is closely related to the soil structure and fertility, and this quantity also interacts with soil erosion and land deterioration (He & Wang, 2019; Lin et al, 2020). Artificial vegetation establishment could affect the soil PSD by (1) ameliorating the stability of the soil structure through roots and (2) effectively increasing soil nutrients and soil coverage via vegetation litter (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, open-type check dams compensate for the shortcomings of closedtype dams due to their unique characteristics, i.e., the trapping of coarse particles and discharge of fine sand and water [5][6][7]. As a novel debris-flow mitigation countermeasure, flexible net barriers, which may be quickly installed with helicopters and dissipate debrisflow energy through elastic and plastic deformation, have been increasingly applied in debris-flow mitigation, especially in the United States and Switzerland [8][9][10][11][12]. However, the impact behavior of debris flows on flexible net barriers is quite different from that on concrete dams because of the nonlinear geometrical characteristics and complicated deformation patterns of flexible net barriers [13][14][15] Many researchers have carried out physical experiments and numerical simulations on debris-flow flexible net barriers.…”
Section: Introductionmentioning
confidence: 99%